Strong plasmon–exciton coupling between lithographically defined single metal nanoparticles and monolayer WSe2 - Yan, Xiaohong; Hong, Wei (Nanoscale, 2020)
Strong coupling between surface plasmons and excitons leads to the formation of plexcitons with new energy states, providing a versatile platform for a range of frontier research subjects. Single plasmonic nanoparticles have recently attracted much attention for realizing strong coupling due to their small mode volume. However, the usually used chemically synthesized metal nanoparticles are unfavorable for accurately tailoring the surface plasmon resonances and adverse to the implementation of on-chip integration. Here, we report for the first time the realization of strong coupling between monolayer WSe2 and lithographically defined single metal nanoparticles. Focusing on gold nanobowties, the large Rabi splitting of 187 meV is achieved. The excitons around the nanogaps in the nanobowties contribute dominantly to the coupling strength, and the coupling strength is larger for smaller nanobowties due to the smaller mode volume. Moreover, the hybrid systems of monolayer WSe2 and gold nanoparticle monomers of nanorods, nanotriangles, and nanodisks are found to closely satisfy the criterion of strong coupling. The strong plasmon–exciton coupling realized by single plasmonic nanostructures fabricated by advanced nanofabrication techniques and monolayer semiconductors can provide new opportunities for manipulating strong light–matter interactions at the nanoscale and facilitate the development of plexciton-based nanodevices with ultrasmall footprints.